Accuracy of the Photometric Redshifts of Brightest Cluster Galaxies Identified in the CFHTLS-W1 - Sinan Aliş (Journal of Advanced Research in Natural and Applied Sciences)
We determine the accuracy of photometric redshifts for the brightest cluster galaxies (BCGs) identified in the W1 field of the Canada-France-Hawaii Telescope Legacy Survey (CFHTLS). BCGs were identified from the galaxy cluster sample produced by the Wavelet Z Photometric (WaZP) cluster finding algorithm between $0.1 < z < 1$. Provided photometric redshifts with the CFHTLS official galaxy catalogs were compared with spectroscopic redshifts from large surveys. 101713 spectroscopic redshifts have been collected from the databases of major spectroscopic surveys. Cross-matching of 3283 BCGs with this large spectroscopic dataset yielded 1215 BCGs with high-quality spectroscopic redshift. These highly reliable spectroscopic redshifts enabled us to determine the photometric redshift accuracy of BCGs as $σ_{NMAD}$=0.020. The outlier fraction is obtained as 1.40%. The dispersion obtained in this study is significantly better than typical photometric redshift accuracies provided in the CFHTLS releases when all types of galaxies are included, which suggests the use of BCGs as a control object when determining galaxy cluster redshifts.